2015 IEEE International Conference on Computer Vision Workshop (ICCVW) 2015
DOI: 10.1109/iccvw.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Articulated Objects from a Moving Camera

Abstract: Many scenes that we would like to reconstruct contain articulated objects, and are often captured by only a single, non-fixed camera. Existing techniques for reconstructing articulated objects either require templates, which can be challenging to acquire, or have difficulties with perspective effects and missing data. In this paper, we present a novel reconstruction pipeline that first treats each feature point tracked on the object independently and incrementally imposes constraints. We make use of the idea t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Recent work has shown that improvements in human pose estimation [13,21,41] and object detection and classification in videos [28,40,47] can be obtained by encoding temporal consistency as part of a larger predictive pipeline. The intuition is that exploiting continuity of motion over video frames can reduce the noise in per-frame predictions.…”
Section: Human Pose Prediction In Videomentioning
confidence: 99%
“…Recent work has shown that improvements in human pose estimation [13,21,41] and object detection and classification in videos [28,40,47] can be obtained by encoding temporal consistency as part of a larger predictive pipeline. The intuition is that exploiting continuity of motion over video frames can reduce the noise in per-frame predictions.…”
Section: Human Pose Prediction In Videomentioning
confidence: 99%
“…Reconstructing articulated objects has attracted a lot of interest during the past decade. Due to the popularity of different image sensors over the years, research focus has gradually shifted from reconstructing 2D skeletons from RGB data [8,9,10,11] to 3D skeletons from RGB [12,13,14,15] or RGB-D data [16,4,17].…”
Section: Related Workmentioning
confidence: 99%
“…In contrast to [18], it is able to reconstruct complex articulated structures. [15] use ray-space optimization to estimate 3D trajectories from 2D trajectories. The approach, however, assumes that the num-ber of parts is known.…”
Section: Related Workmentioning
confidence: 99%